The choice of institutions to solve cooperation problems: A survey of experimental research - Astrid Dannenberg; Carlo Gallier (Philipps-University Marburg, School of Business and Economics, 2019)
A growing experimental literature studies the endogenous choice of institutions to solve cooperation problems arising in prisoners' dilemmas, public goods games, and common pool resource games. Participants in these experiments have the opportunity to influence the rules of the game before they play the game. In this paper, we review the experimental literature of the last 20 years on the choice of institutions and describe what has been learned about the quality and the determinants of institutional choice. Almost all institutions improve cooperation if they are implemented, but they are not always implemented by the players. Institutional costs, remaining free-riding incentives, and a lack of learning opportunities are the most important barriers. At the individual level, own cooperativeness and beliefs about other players' behavior can be identified as important determinants of institutional choice. Cooperation tends to be higher under endogenously chosen institutions than exogenously imposed institutions. However, a significant share of players fails to implement the institution and they often perform poorly, which is why we cannot conclude that letting people choose is better than enforcing institutions from outside.
Keywords: C71; C91; C92; D02; D70; H41; 330; Literature review; experiments; cooperation; public goods; endogenous institutional choice; voting